Assessment of depression and its correlates among college students in Rishikesh Uttarakhand - Kumar, Santosh; Natarajan, Kavitha; B, Yogesh; Chandra, Rishita (Indian Journal of Community Health, 2019)
Background: Depression is a major contributor to the overall global burden of disease and is the leading cause of disability worldwide. Objective: To assess the levels of depression and its correlate among college students in Rishikesh, Uttarakhand. Methodology: Community based cross sectional study was conducted from February 2018 to April 2018 among 126 students of a Government PG College Rishikesh belonging to age 18 -26 years. A pre-validated semi- structured pretested Physical Health Questionnaire (PHQ-9) was applied for this purpose. Results: Mean age of the participants was 22.84±1.5 years. Overall prevalence of depression among study population was 74.60% among them 4% were severely depressed. 58% of females and 40% males had suicidal ideations. Majority of participants were stressed with the undue peer pressure followed by career pressure. Physical activity for atleast 30 minutes a day for 5 days in a week was found to be significantly (p<0.02, odds ratio 0.20 (0.06-0.7 at 95%CI) beneficial for depression. Conclusion: Depression is prevalent among college going population. Peer pressure, academic stress, career pressure, financial stress in home, undue parental expectations on students are associated with depression among college going students.